Violence Against Teachers and Work Ability: A Cross-Sectional Study in Northeast Brazil - Ceballos, Albanita G. C. de (Journal of interpersonal violence, 2021)
This study aimed to describe teacher work ability in relation to violence against teachers and certain sociodemographic and occupational features. A cross-sectional study investigated 525 kindergarten and elementary grade school teachers from Jaboatão dos Guararapes, Northeast Brazil. Information from each teacher was collected through a self-administered questionnaire. The main outcome was teacher reports about their current and future (in 2 years’ time) physical and emotional work ability. The teachers were predominantly female, young, with heavy workloads and on low incomes. Teachers reported being victimized in the school by physical violence (22.9%), verbal violence (42.9%), theft or robbery (36.4%), aggression or threats with a firearm or a non-firearm weapon (knife, glass, etc.; 7.0%), or by some form of violence (58.4%). Teachers reported low physical (56.0%) and emotional (40.6%) current work ability. Low physical work ability was significantly associated with physical and verbal violence, theft and robbery, and some form of violence; low emotional work ability was associated with physical and verbal violence, aggression or threat with a weapon, and some form of violence. Expectation of low work ability in the future was reported by 42.9% of the teachers and was associated with higher education level, and physical violence, verbal violence, theft or robbery, aggression or threat with a weapon, and some form of violence. The association between violence and work ability was modified by education level. Subsequent control of confounding in the strata of education confirmed the associations between violence and low work ability. The physical, emotional, and future work ability of teachers was low and associated with school violence, indicating the need to promote a safer work environment inside the school and in society as a whole.